Increasing Student Engagement through Authentic Learning Activities in MOOC Environment - Junaini, S.N.; Abdullah, J.; Bujang, Y.R.; Fauzi, A.H.; Sidi, J. (2018)
Learner engagement is one of the most principal factor that determines the effectiveness on MOOC. From the study, we found that most of the students gave positive comments especially on the learning activities. Overall, positive comments were received especially in terms of active interaction from the instructor.